Operating a Webshop in Rural Areas - Péntek, Ádám; Botos, Szilvia; Füzesi, István (International Journal of Engineering and Management Sciences, 2018)
The importance of e-commerce in Hungary is unquestionable. 66% of the population is regular internet users (I3), every fourth person uses it on a daily basis. Online sales have increased from 137 billion HUF in 2010 to 427 billion HUF in 2016, while offline sales were not able to reach this growth (I1). Undoubtedly, online sale has become a very valuable market. The age group really valuable as consumers spends about 6 hours a day online, out of which 3 hours are active usage (I2). The Internet is also the most important source of information and keeping in contact, as 41% of the population uses it method. The availability of the Internet in Hungary is literally independent of the geographic location, thanks to the Digital Renewal Action Plan in Hungary’s current strategy, as one of its main chapters is "Enhanced and Secure Infrastructure for All." (Botos 2013) plan. There are many unfavorable processes in Hungary’s rural areas. Of these, emigration and the abandonment of the local economy are outstanding. To stop these processes, the "National Rural Strategy" (2012-2020) was created. Its most important areas are employment growth, balanced and diverse land and forest management, production structure, restoration of local food production and food markets, local energy production, strengthening the local communities, improvement of population patterns and conservation of natural systems and the biodiversity. The integration of rural economies into the on-line marketplace and their linkage to different DBEs not only vertically but horizontally can be one of the keys to their survival and development. The situation of businesses on the on-line marketplace in the countryside is very special. On the one hand, they are more favourable in many aspects of their operation, but in some cases they have disadvantages that fundamentally threaten their survival. The purpose of this article is to get to know this environment, map its benefits and drawbacks. For this, we use the results of in-depth interviews conducted with businesses operating on an on-line market in rural settlements.